Encapsulamento de [beta]-caroteno em nanotubos de carbono utilizando modelagem molecular - Moreira, Edvan (2008)
From its discovery, the nanotubes of carbon are seen as material’s highly promising for a lot of applications. The combination of nanotubes of carbon with other molecules is the most general form of modifying their properties. New methods to control and to tune these properties are necessary for the developing of their potentials applications. The functionalization has been proposed as one of the processes capable to modify the optical properties of the nanotubes of carbon, through chemical reaction ”it is arrested”another molecule in the surface of the nanotube. However, another more elegant form of functionalization is through the encapsulation of molecules inside the nanotube. Recently, the encapsulation of the molecule of the beta-carotene experimentally in nanotubes of carbon was accomplished and changes were verified in the absorption spectrum. In this work we performed simulations of molecular dynamics using field of similar universal force to test the encapsulation of the beta-carotene, and calculations of Electronic Structure to verify charge transference. The obtained results of the molecular dynamics confirm that the encapsulation of the -carotene happens in the three cases studied experimentally by Yanagi and collaborators.